Protection of human podocytes from Shiga toxin 2-induced phosphorylation of mitogen-activated protein kinases and apoptosis by human serum amyloid P component - Dettmar, Anne K.; Binder, Elisabeth; Greiner, Friederike R.; Liebau, Max C.; Kurschat, Christine E.; Jungraithmayr, Therese C.; Saleem, Moin A.; Schmitt, Claus P.; Feifel, Elisabeth; Orth-Höller, Dorothea; Kemper, Markus J.; Pepys, Mark; et al. (Infection and immunity, 2014)
Hemolytic uremic syndrome (HUS) is mainly induced by Shiga toxin 2 (Stx2)-producing Escherichia coli. Proteinuria can occur in the early phase of the disease, and its persistence determines the renal prognosis. Stx2 may injure podocytes and induce proteinuria. Human serum amyloid P component (SAP), a member of the pentraxin family, has been shown to protect against Stx2-induced lethality in mice in vivo, presumably by specific binding to the toxin. We therefore tested the hypothesis that SAP can protect against Stx2-induced injury of human podocytes. To elucidate the mechanisms underlying podocyte injury in HUS-associated proteinuria, we assessed Stx2-induced activation of mitogen-activated protein kinases (MAPKs) and apoptosis in immortalized human podocytes and evaluated the impact of SAP on Stx2-induced damage. Human podocytes express Stx2-binding globotriaosylceramide 3. Stx2 applied to cultured podocytes was internalized and then activated p38α MAPK and c-Jun N-terminal kinase (JNK), important signaling steps in cell differentiation and apoptosis. Stx2 also activated caspase 3, resulting in an increased level of apoptosis. Coincubation of podocytes with SAP and Stx2 mitigated the effects of Stx2 and induced upregulation of antiapoptotic Bcl2. These data suggest that podocytes are a target of Stx2 and that SAP protects podocytes against Stx2-induced injury. SAP may therefore be a useful therapeutic option.
Gesehen am 21.10.2020